COMPUTING THE MODIFIED ECCENTRIC CONNECTIVITY POLYNOMIAL OF NAPHTHYLENIC LATTICES - VEYLAKI, Maryam; NIKMEHR, Mohammad Javad (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Let there be a graph, where is a non-empty set of vertices and is a set of edges. In such chemical graphs, the vertices of the graph corresponds to the atoms of the molecule, and the edges represent the chemical bonds. The aim of this paper is to compute the modified eccentric connectivity polynomial for the naphthylenic Let be a graph, where is a non-empty set of vertices and is a set of edges. In such chemical graphs, the vertices of the graph corresponds to the atoms of the molecule, and the edges represent the chemical bonds. The aim of this paper is to compute the modified eccentric connectivity polynomial for the naphthylenic molecular graph.molecular graph.